QUANTIFICATION OF CD1A+ LANGERHANS CELLS IN ORAL EPITHELIAL DYSPLASIA AND ORAL SQUAMOUS CELL CARCINOMA - Babar, Sardar Waleed; Asif, Muhammad; Zaheer, Farwa; Ameer, Amna; Haroon, Azka; Minhas, Sadia (Journal of Ayub Medical College Abbottabad, 2025)
Background: To quantify the immunohistochemical expression of CD1a positive Langerhans cell population and find their association with tumour progression in oral epithelial dysplasia and oral squamous cell carcinoma. Methods: A total of 119 biopsies were collected out of which 61 were oral epithelial dysplasia (20 mild, 20 moderate, 21 severe) and 58 were oral squamous cell carcinoma (well differentiated only). Fresh haematoxylin and eosin slides were prepared followed by application of CD1a immunohistochemical marker to quantify Langerhans cell in epithelium and connective tissue separately. To compare quantitative results One Way ANOVA and Independent Sample T test was used. ≤0.05 was considered a significant p-value. Results: A statistically significant association between CD1a+ Langerhans cell count and advancing degrees of dysplasia to well differentiated oral squamous cell carcinoma in both epithelium (<0.05) and connective tissue (<0.05) was seen. Significant difference was also seen when oral epithelial dysplasia was compared with well differentiated oral squamous cell carcinoma in epithelium (p<0.05) but, no significant difference (p>0.05) was seen in case of connective tissue. Conclusion: The mean CD1a+ Langerhans cell count decreased with increase in degree of dysplasia and an increase in well differentiated oral squamous cell carcinoma was seen which needs further studies. Mean CD1a+ LC count can be used as a tool for highlighting disease progression for epithelial dysplasia and increase in mean CD1a+ Langerhans cell in oral squamous cell carcinoma can be argued with its better prognosis among other histological grades of this carcinoma.